Affinity of Indocyanine Green in the Detection of Colorectal Peritoneal Carcinomatosis: The Role of Enhanced Permeability and Retention Effect. (April 2017) - Filippello, Alexandre; Porcheron, Jack; Klein, Jean Philippe; Cottier, Michèle; Barabino, Gabriele
Indocyanine green (ICG) is increasingly being used in digestive oncology. In colorectal cancer, ICG can be used to detect lymph node metastasis and hepatic metastasis on the surface of the liver. In peritoneal carcinomatosis, it was previously suspected that the diffusion of ICG in the tumor mass was due to the enhanced permeability and retention effect; however, this phenomenon has not been clearly demonstrated. Using bevacizumab, an antibody directed against vascular endothelial growth factor that consequently inhibits neoangiogenesis, we sought to confirm the mode of ICG diffusion. We compared the fluorescence of peritoneal carcinomatosis nodules from patients who had previously received bevacizumab during their oncologic treatment with those who did not receive this therapy. The sensitivity of the carcinomatosis nodule fluorescence was higher in the patients who did not receive bevacizumab compared with those who received the drug (76.3% and 65.0%, respectively). The rate of false-negative results was higher in the bevacizumab group than in the group that did not receive the drug (53.8% and 42.9%, respectively). Using bevacizumab, we demonstrate that the enhanced permeability and retention effect causes ICG accumulation in peritoneal carcinomatosis resulting from colorectal cancer.